2015
DOI: 10.3109/07853890.2015.1075063
|View full text |Cite
|
Sign up to set email alerts
|

Natural course of Finnish gelsolin amyloidosis

Abstract: The first symptom was ophthalmological in most cases. Except for CLD no prominent difference in the age of appearance was found between the major symptoms. CTS, cardiac pacemakers, and cardiomyopathy were remarkably more common compared to the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(59 citation statements)
references
References 28 publications
2
57
0
Order By: Relevance
“…Clinical manifestations including seizures, multiple cerebral cavernous malformation, and hemorrhagic lesions in the proband's brain, and multiple cerebral cavernous malformation lesions in his mother's brain, complied with most of the common symptoms of FGA, suggesting that the patients might have FGA (Kiuru-Enar et al, 2002). The presence of the heterozygous G duplicate in exon1 (c.100dupG) of the GSN gene further supports that the disease of these patients was GSN mutation-mediated FGA (Kiuru-Enar et al, 2002;Kwiatkowski et al, 1988;Nikoskinen et al, 2015). The presence of these clinical manifestations and the mutation in the GSN gene in the proband and his mother, and the presence of the mutation in GSN without any clinical manifestation in the proband's daughter, support the observations that FGA develops at different paces in different patients (Atula, 2016).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Clinical manifestations including seizures, multiple cerebral cavernous malformation, and hemorrhagic lesions in the proband's brain, and multiple cerebral cavernous malformation lesions in his mother's brain, complied with most of the common symptoms of FGA, suggesting that the patients might have FGA (Kiuru-Enar et al, 2002). The presence of the heterozygous G duplicate in exon1 (c.100dupG) of the GSN gene further supports that the disease of these patients was GSN mutation-mediated FGA (Kiuru-Enar et al, 2002;Kwiatkowski et al, 1988;Nikoskinen et al, 2015). The presence of these clinical manifestations and the mutation in the GSN gene in the proband and his mother, and the presence of the mutation in GSN without any clinical manifestation in the proband's daughter, support the observations that FGA develops at different paces in different patients (Atula, 2016).…”
Section: Discussionmentioning
confidence: 73%
“…These point mutations cause defective folding of GSN protein, which makes the protein accumulate as GSN amyloid in various tissues. GSN mutations have been found in all molecular genetically characterized FGA patients in Finland (Nikoskinen, Schmidt, Strbian, Kiuru-Enari, & Atula, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Corneal lattice dystrophy with amyloid deposits (type 2) is usually the first HGA sign in the third life decade, presenting with reduced corneal sensitivity, corneal erosions, and dry eye syndrome (Carrwik and Stenevi, ; Nikoskinen et al, ) . In our cases, ocular symptoms were mild or absent, corneal lattice dystrophy was not diagnosed before facial palsy and was revealed only by ophthalmologic evaluation when specifically looked for.…”
Section: Discussionmentioning
confidence: 99%
“…Other neurological and systemic features may occur (Meretoja, ; Kiuru‐Enari and Haltia, ) . The disease was first described in Finland where there is the largest number of patients (Nikoskinen et al, ) , although several cases have been reported from other countries (Conceição et al, ; Lüttmann et al, ; Solari et al, ; Taira et al, ; Alabdali et al, ; Park et al, ) . Two main mutations in the same nucleotide on GSN have been described so far, resulting in amino acid substitution and alteration of the primary structure of gelsolin (Levy et al, ; de la Chapelle et al, ) .…”
Section: Introductionmentioning
confidence: 99%
“…Exclusion criteria for the study population were (1) age below 50 years, (2) implanted cardiac pacemaker, (3) claustrophobia, and (4) implanted metal objects that could interfere with CMR. Patients selected were older than 50 years due to disease progression beginning at an older age [1]. …”
Section: Methodsmentioning
confidence: 99%